2016
DOI: 10.1016/j.celrep.2016.07.006
|View full text |Cite
|
Sign up to set email alerts
|

A Transcript-Specific eIF3 Complex Mediates Global Translational Control of Energy Metabolism

Abstract: The multisubunit eukaryotic translation initiation factor eIF3 is thought to assist in the recruitment of ribosomes to mRNA. The expression of eIF3 subunits is frequently disrupted in human cancers, but the specific roles of individual subunits in mRNA translation and cancer remain elusive. Using global transcriptomic, proteomic, and metabolomic profiling, we found a striking failure of Schizosaccharomyces pombe cells lacking eIF3e and eIF3d to synthesize components of the mitochondrial electron transport chai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
65
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(78 citation statements)
references
References 58 publications
13
65
0
Order By: Relevance
“…Consistently, c-JUN mRNA was translationally induced during acute ER stress (Tg:1h, Figure S2), with concomitant increase in eIF3d:c-JUN mRNA binding (Figure 4C), and remained efficiently translated during chronic ER stress (Tg:16h, Figure S2). In S. pombe , loss of therein non-essential eIF3e and eIF3d subunits prevented synthesis of the mitochondrial electron transport chain components leading to respiration defect (Shah et al, 2016). eIF3e, which is essential in higher eukaryotes (Wagner et al, 2014), was also suggested to promote translation of similar mRNAs, thereby raising the possibility that eIF3 – via its eIF3d-eIF3e module – may orchestrate an mRNA-specific translational mechanism controlling energy metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…Consistently, c-JUN mRNA was translationally induced during acute ER stress (Tg:1h, Figure S2), with concomitant increase in eIF3d:c-JUN mRNA binding (Figure 4C), and remained efficiently translated during chronic ER stress (Tg:16h, Figure S2). In S. pombe , loss of therein non-essential eIF3e and eIF3d subunits prevented synthesis of the mitochondrial electron transport chain components leading to respiration defect (Shah et al, 2016). eIF3e, which is essential in higher eukaryotes (Wagner et al, 2014), was also suggested to promote translation of similar mRNAs, thereby raising the possibility that eIF3 – via its eIF3d-eIF3e module – may orchestrate an mRNA-specific translational mechanism controlling energy metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…One candidate mechanism involves the translation initiation factor 3 complex, which has a role in regulating the translation initiation of mitochondrial-localized proteins across eukaryotes. In 5. pombe , subunits eIF3d/e promote the synthesis of mitochondrial electron transfer chain proteins through a TL-mediated mechanism (76). InS.…”
Section: Discussionmentioning
confidence: 99%
“…Their findings suggest that depletion of eIF3e triggers a metabolic switch that increases dependence on glycolysis, as respiratory deficiencies alongside increased sensitivity to oxidative stress are also observed when eIF3d is depleted in addition to eIF3e knockdown. Essentially, this data suggests that the novel function of eIF3d-eIF3e in maintaining mitochondrial respiration components and serving to adjust metabolic pathways may help us better understand how the cancer-promoting properties of the eIF3 complex emerge [127].…”
Section: In Breast Cancer Cells Reduction Of Eif3e Expression Bymentioning
confidence: 92%
“…Furthermore, a recent study suggests the role of eIF3d-eIF3e module within the eIF3 complex that regulates the translation of specific mRNAs involved in maintaining metabolic pathways that are likely disrupted in cancer cells [127]. Critical components of the mitochondrial electron transport chain were downregulated in both yeast and mammalian cells (nontumorigenic: MCF-10A and nontumorigenic: MCF7) that were eIF3e-depleted using siRNA, whereas glucose metabolism and amino acid biosynthesis processes were upregulated.…”
Section: In Breast Cancer Cells Reduction Of Eif3e Expression Bymentioning
confidence: 99%